Scalable Business Models for Alternative Biomass Cooking Fuels and Their Potential in Sub-Saharan Africa - Hosier, Richard (World Bank, Washington, DC, 2017)
Building on its previous work on clean cooking in Africa, the World Bank has begun to explore intervention strategies for the clean cooking sector that move beyond stoves to examine the potential for cleaner-burning biomass fuels. This report focuses on the potential for scaling biofuel markets in the region for cooking as opposed to heating or industrial uses, specifically carbonized and uncarbonized biomass briquettes, biomass pellets, ethanol fuel, and ethanol gel. Models are explored for scaling the cooking fuel value chains while balancing the environmental health, social, and economic impacts of the fuels at the household and national level. While this report focuses solely on pellets, briquettes, and ethanol, referred to here as alternative biofuels, LPG, electricity, and biogas also have a role to play in a clean cooking ecosystem.